1999
DOI: 10.1111/j.1553-2712.1999.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

The Informed Consent Process and the Use of the Exception to Informed Consent in the Clinical Trial of Diaspirin

Abstract: Abstract. In the clinical trial of diaspirin crosslinked hemoglobin (DCLHb), optimal therapy required the immediate enrollment of patients with severe, uncompensated, traumatic hemorrhagic shock. When it was not feasible to obtain prospective consent, an exception to informed consent was used according to FDA regulation 21 CFR 50.24. Objectives: To examine the informed consent process and the use of the consent exception and consent to continue (CTC), and to describe the patients for whom this process was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…13,22,23,25 Some recommend that the amount of required community consultation or public disclosure activities should be based on the incremental risks of a study. 10,34,35 Although most EFIC studies have the potential to enroll anyone from the entire community, some studies are more likely to enroll patients with a particular risk factor and thus may be targeted.…”
Section: Discussionmentioning
confidence: 99%
“…13,22,23,25 Some recommend that the amount of required community consultation or public disclosure activities should be based on the incremental risks of a study. 10,34,35 Although most EFIC studies have the potential to enroll anyone from the entire community, some studies are more likely to enroll patients with a particular risk factor and thus may be targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential for psychological harm is real, few patients/surrogates have opted to discontinue participation in RCTs that have been carried out without informed consent in recent years, and investigators have not reported adverse reactions from patients or their surrogates (37)(38)(39)(40)(41)(42). However, little data exist about the specific responses of research participants and/or their families on learning about research that was conducted in the absence of informed consent.…”
Section: Potential Sources Of Psychological Harm From Rct Participationmentioning
confidence: 95%
“…Moreover, identifying potential subjects a priori or their legally authorized representatives (LARs) in a timely fashion may not be practical in most circumstances. 2,3 …”
mentioning
confidence: 99%